Sosialisai Aplikasi Hello English Kids kepada Ibu PKK RW 10 Kampung Tengah - Ria Saraswati; Tiarma Ika Yuliana (J-ABDIPAMAS (Jurnal Pengabdian Kepada Masyarakat), 2020)
ABSTRACTThe learning process especially for learning English will be more fun, not boring and easy to understand for children if it uses the right learning media which can foster children’s reading and writing abilities. Learning media is a tool that serves to convey learning messages. Media in learning has a function as a tool to clarify the message conveyed by the teacher. The media also functions for individual learning where the position of the media fully serves the learning needs of students. Multimedia is one source of teaching or alternative media in learning English that can integrate and link elements of the human physical environment in the dimensions of space. It predicts one of the interactive multimedia learning that to improve children’s reading and writing abilities is the learning media in a mobile phone application called Hello English Kids: Learn English. Hello English Kids Media: Learn English predicted to improve children’s reading and writing skills because this media teaches English to children in a fun, effective way and can build a strong foundation for their language development so it can attract attention, curiosity, arouse enthusiasm and fun for children.Keywords: reading, writing, multimediaABSTRAKProses pembelajaran khususnya untuk pembelajaran Bahasa Inggris akan lebih menyenangkan, tidak membosankan dan lebih mudah dipahami anak jika menggunakan media pembelajaran yang tepat yaitu media yang dapat menumbuhkan kemampuan membaca dan menulis anak. Media pembelajaran adalah sebuah alat yang berfungsi untuk menyampaikan pesan pembelajaran. Media dalam pembelajaran memiliki fungsi sebagai alat bantu untuk memperjelas pesan yang disampaikan guru. Media juga berfungsi untuk pembelajaran individual di mana kedudukan media sepenuhnya melayani kebutuhan belajar siswa. Multimedia adalah salah satu sumber pengajaran atau media alternatif dalam pembelajaran Bahasa Inggris yang dapat memadukan dan mengaitkan unsur lingkungan fisik manusia dalam dimensi ruang. Salah satu multimedia interaktif pembelajaran yang diprediksikan dapat meningkatkan kemampuan membaca dan menulis anak adalah media pembelajaran yang terdapat dalam aplikasi telepon seluler bernama Hello English Kids: Learn English. Media Hello English Kids: Learn English di prediksikan dapat meningkatkan kemampuan membaca dan menulis anak karena media ini mengajarkan Bahasa Inggris kepada anak dengan cara yang menyenangkan, efektif dan dapat membangun fondasi kuat untuk pengembangan bahasa mereka sehingga dapat menarik perhatian, rasa keingintahuan, membangkitkan semangat serta menyenangkan bagi anak.Kata kunci: membaca, menulis, multimedia